2021
DOI: 10.1155/2021/5514674
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Approach for the Reliability Evaluation of Electric Connector

Abstract: Under the trend of high density and miniaturization, the current that the connector transmits per unit volume is getting higher and higher, which makes the reliability design of the connector more challenging. Under the pressure of high performance and low cost requirements, the design has to be more accurate and more efficient. Thus, in the design process, a systematic approach for reliability evaluation is required. However, there is no valid enough approach that is integrated, well-organized, and quantitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…It must make electrical contact between the ECU pins to which it belongs, and the surrounding world. If this minimum requirement cannot be met, then the system no longer works, potentially having disastrous consequences [6].…”
Section: Figure 2: the Connectors From The Dutmentioning
confidence: 99%
“…It must make electrical contact between the ECU pins to which it belongs, and the surrounding world. If this minimum requirement cannot be met, then the system no longer works, potentially having disastrous consequences [6].…”
Section: Figure 2: the Connectors From The Dutmentioning
confidence: 99%
“…Ren et al 7 summarized some problems of physical failure model and reliability assessment of circular electrical connectors, and proposed a new method combining accelerated degradation test and physical failure modeling. Wang et al 8 proposed a systematic method for the reliability assessment of connector and verified the effectiveness of the method by applying it to leaf spring connectors, and verified the effectiveness of the method by applying it on blade-spring connector. However, a large number of test data showed that the degradation rate of different aperture contact pairs has difference in the same test environment.…”
Section: Introductionmentioning
confidence: 99%